Marwar under Jaswant Singh, (1658-1678) = Jodhpur hukumat ri Bahi - Chandra, Satish; Sinh, Raghubir, 1908-; Sharma, G. D. (Ghanshyam Datt), 1943- (Meenakshi Prakashan, 1976)
Contemporary eyewitness account.